2007
DOI: 10.1073/pnas.0704901104
|View full text |Cite
|
Sign up to set email alerts
|

Pseudomonas syringae type III effector AvrRpt2 alters Arabidopsis thaliana auxin physiology

Abstract: The Pseudomonas syringae type III effector AvrRpt2 promotes bacterial virulence on Arabidopsis thaliana plants lacking a functional RPS2 gene (rps2 mutant plants). To investigate the mechanisms underlying the virulence activity of AvrRpt2, we examined the phenotypes of transgenic A. thaliana rps2 seedlings constitutively expressing AvrRpt2. These seedlings exhibited phenotypes reminiscent of A. thaliana mutants with altered auxin physiology, including longer primary roots, increased number of lateral roots, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
251
0
6

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 333 publications
(263 citation statements)
references
References 65 publications
6
251
0
6
Order By: Relevance
“…Similar to the plant defense hormones SA and jasmonic acid, auxin differentially regulates the outcomes of plant-pathogen interactions depending on the life styles of the pathogens (Kazan and Manners, 2009;Robert-Seilaniantz et al, 2011). During infection by Pst, the free indole acetic acid level increased and application of auxin promoted disease symptom development (O'Donnell et al, 2003;Chen et al, 2007;Wang et al, 2007). Consistently, the type III effector AvrRpt2 modulates host auxin physiology and signaling as a potential virulence strategy (Chen et al, 2007).…”
Section: Discussionmentioning
confidence: 72%
See 4 more Smart Citations
“…Similar to the plant defense hormones SA and jasmonic acid, auxin differentially regulates the outcomes of plant-pathogen interactions depending on the life styles of the pathogens (Kazan and Manners, 2009;Robert-Seilaniantz et al, 2011). During infection by Pst, the free indole acetic acid level increased and application of auxin promoted disease symptom development (O'Donnell et al, 2003;Chen et al, 2007;Wang et al, 2007). Consistently, the type III effector AvrRpt2 modulates host auxin physiology and signaling as a potential virulence strategy (Chen et al, 2007).…”
Section: Discussionmentioning
confidence: 72%
“…Consistent with auxin's role in plant disease resistance, we have found that the P. syringae effector AvrRpt2 augments host auxin biosynthesis and signaling and alters auxin physiology (Chen et al, 2007). Transgenic Arabidopsis plants expressing AvrRpt2 exhibit phenotypes reminiscent of auxin mutants with altered auxin physiology, including elongated primary roots and increased numbers of lateral roots, increased response to exogenously applied auxin, and enhanced accumulation of free indole acetic acid during P. syringae infection (Chen et al, 2007).…”
mentioning
confidence: 64%
See 3 more Smart Citations